Review of high recovery concentrate management options - Leong, J.; Tan, Jace; Charrois, Jeffrey; Ladewig, B. (Taylor & Francis Ltd., 2013)
Current methods of inland concentrate disposal include surface water discharge, deep-well injection and evaporation ponds. These methods are unsustainable and are limited by high capital cost and non-ubiquitous applications. This paper gives an overview of potential alternatives and technologies available that can reduce the concentrate formed via reducing its volume or recycling. Potential alternatives explored have been electrodialysis, mechanical evaporation, vibratory shear-enhanced process (VSEP) and wind-aided intensification of evaporation. All technologies have potential for use in areas distant from the coast and have better performance than currents management techniques. This paper reviews multiple studies that have explored alternate technologies for concentrate disposal in terms of economics and feasibility. Of the five case studies presented, VSEP shows promise as a secondary system of treatment via enhancing percentage recovery; higher permeate flux and lower operational costs.